2021
DOI: 10.3390/rs13020183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Lockdown on the Fisheries Sector: A Case Study from Three Harbors in Western India

Abstract: The COVID-19 related lockdowns have brought the planet to a standstill. It has severely shrunk the global economy in the year 2020, including India. The blue economy and especially the small-scale fisheries sector in India have dwindled due to disruptions in the fish catch, market, and supply chain. This research presents the applicability of satellite data to monitor the impact of COVID-19 related lockdown on the Indian fisheries sector. Three harbors namely Mangrol, Veraval, and Vankbara situated on the nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 30 publications
(32 reference statements)
0
34
0
1
Order By: Relevance
“…Our study relied on reported increases in effort; future studies could use remote sensing and fisheries yield data to triangulate these observations. Using remote sensing data to investigate changes in the area covered by fishing boats in harbor (instead of out to sea), Avtar et al, (2021) estimated that a quarter of the annual fish production was lost due to COVID-19 across three key harbors in India.…”
Section: Discussionmentioning
confidence: 99%
“…Our study relied on reported increases in effort; future studies could use remote sensing and fisheries yield data to triangulate these observations. Using remote sensing data to investigate changes in the area covered by fishing boats in harbor (instead of out to sea), Avtar et al, (2021) estimated that a quarter of the annual fish production was lost due to COVID-19 across three key harbors in India.…”
Section: Discussionmentioning
confidence: 99%
“…Remote sensing has also been used to detect macro-level transformations like land cover changes due to human displacement as well as to setup an association among the land tenure and land use land cover (LULC) classification [55]. If remote sensing techniques are cautiously applied within the limits of measurement validity and selection biases, then it is also possible to estimate the cultural loss, agricultural losses, land degradation and rehabilitation, disruption of water resources, and change in vegetation [33,35,56]. Using multiple satellite images and other explanatory variables, Levin et al [57] indicated that more than 5% of 1073 World Heritage Sites (WHS) were in danger because of severe internal conflicts in which 25 are caused by armed conflicts.…”
Section: Remote Sensing In Armed Conflictsmentioning
confidence: 99%
“…8 Avtar et al 2021. explained in their article that India's blue economy and small-scale fisheries are disrupted during the covid phase due to disruption in the fish catch, market, and supply chain. 9 Similarly, Parampriya et al 2020 discussed on challenges of fisherfolk women of Puducherry during covid 19 and observed several cases and concluded that lockdown affects the economy of the house of fisherwomen so that they cannot buy proper food for their family and create stress, anxiety about their future. 10 Sunny et al 2021 extensively studied fisheries in Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 99%